Teachers’ professional competence profile dataset during implementation of Merdeka curriculum - Maryani, Ika; Irsalinda , Nursyiva; Jaya , Patria Handung; Sukma, Hanum Hanifa; Raman , Arumugam L. (Universitas Ahmad Dahlan, 2024)
The Merdeka curriculum serves as a mechanism for enhancing the quality of education in Indonesia. Effective utilization of professional competence among educators can expedite the success of the Merdeka curriculum. However, the challenges associated with the Merdeka curriculum, as encountered by educators, are multifaceted and demand a high level of professionalism for resolution. This study aims to scrutinize teachers' professional competence concerning the design of learning activities within the Merdeka curriculum. It constitutes a quantitative descriptive study involving 205 primary school teachers from Indonesia. A semantic differential scale, administered through a Google Form, was employed to gather data on professional competence, comprising three indicators and 12 questions. The validity of the instrument was assessed using Pearson correlation, and reliability was determined using Cronbach's alpha. This investigation encompassed a series of cluster analysis procedures. The research has yielded significant insights into the professional competence of teachers during the implementation of the Merdeka curriculum in Indonesia. The categorization of teachers' professional competence reveals a prevalence of moderate to high competence, with a minority exhibiting low competence. These findings underscore the necessity for attention from governmental bodies and other stakeholders. Prioritizing training and sustainable professional development through collaborative learning communities emerges as imperative. Areas identified for enhancement encompass an understanding of student characteristics and pedagogical methodologies, mastery of learning content, and proficiency in curriculum development and implementation.